Democracy and the Preparation and Conduct of War. Issue 3 (2021) - Crawford, Neta C.
Abstract: In Ethics, Security, and the War-Machine, Ned Dobos highlights several negative consequences the preparation for war has for individuals and states. But he misses what I consider perhaps the most significant consequence of military mobilization for states, especially democracies: how war and the preparation for it affect deliberative politics. While many argue that all states, including democracies, require strong militaries—and there is some evidence that long wars can build democracies and states—I focus on the other effects of militarization and war on democratic states. War and militarism are antipodal to democracy and undermine it. Their normative bases are conflicting—democracy takes force off the table, whereas force is legitimate in war. Thus, while militarism and militarization can sometimes yield liberalization and the expansion of civil rights, they are arguably more likely to undermine democratic norms and practices.